2023
DOI: 10.3389/fmicb.2023.1072053
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes during torpor favor association with Endozoicomonas endosymbionts in the urochordate Botrylloides leachii

Abstract: Environmental perturbations evoke down-regulation of metabolism in some multicellular organisms, leading to dormancy, or torpor. Colonies of the urochordate Botrylloides leachii enter torpor in response to changes in seawater temperature and may survive for months as small vasculature remnants that lack feeding and reproductive organs but possess torpor-specific microbiota. Upon returning to milder conditions, the colonies rapidly restore their original morphology, cytology and functionality while harboring re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Endozoicomonas are conspicuous chemoorganoheterotrophic Gammaproteobacteria found in a wide range of animal hosts, including coral, sponges, and fish (reviewed in Neave et al, 2016 ). In ascidians, Endozoicomonas are also prevalent (Galià‐Camps et al, 2023 ; Hyams et al, 2023 ; Schreiber et al, 2016 ) and phylogenetic analyses of 16S rRNA genes have revealed an ascidian‐specific clade (Schreiber et al, 2016 ). Members of the same ascidian‐specific Endozoicomonas clade were also detected in seawater, albeit at much lower abundances, suggesting a facultative symbiosis (Schreiber et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endozoicomonas are conspicuous chemoorganoheterotrophic Gammaproteobacteria found in a wide range of animal hosts, including coral, sponges, and fish (reviewed in Neave et al, 2016 ). In ascidians, Endozoicomonas are also prevalent (Galià‐Camps et al, 2023 ; Hyams et al, 2023 ; Schreiber et al, 2016 ) and phylogenetic analyses of 16S rRNA genes have revealed an ascidian‐specific clade (Schreiber et al, 2016 ). Members of the same ascidian‐specific Endozoicomonas clade were also detected in seawater, albeit at much lower abundances, suggesting a facultative symbiosis (Schreiber et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis revealed the presence of Endozoicomonas microcolonies on the branchial sac of most of the ascidian species investigated (Schreiber et al, 2016 ). In addition, resting colonies of B. leachii were enriched with a novel lineage of Endozoicomonas that appear to occupy specific hemocytes found exclusively in resting animals (Hyams et al, 2023 ). Here, we observed a decrease in the relative abundance of Endozoicomonas in the resting forms of P. constellatum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on another botryllid ascidian has revealed that under stress conditions that lead to a torpor state, a novel lineage of the commensal bacterium Endozoicomonas, was dominant in torpor animals, and potentially occupied hemocyte types that were only detected in torpid animals [61]. This bacterial symbiont is found in close association with diverse marine invertebrate hosts, including reef-building corals, sponges, bryozoans, sea slugs, and other tunicates [62][63][64][65][66].…”
Section: Proteome Differences Between B Schlosseri Laboratory and Fie...mentioning
confidence: 99%